2013
DOI: 10.5455/2320-6012.ijrms20131127
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of dengue virus in a tertiary care hospital, Andhra Pradesh, South India

Abstract: Background: Dengue fever and Dengue Haemorrhagic fever (DF/DHF) is an acute viral disease caused by Dengue virus. The infection is transmitted by the bite of an infected female mosquito- Aedes aegypti. The Dengue virus causes significant morbidity and mortality in many parts of the world, including India, where it was first isolated in Calcutta, West Bengal during 1945. This study was conducted to know the seroprevalence of Dengue virus in a tertiary care hospital, Hyderabad Methods: Blood for serological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The prevalence rate of 17.2% from this study is lower than what Faneye et al (2013) who reported 30.8% among the population studied in Nigeria. Likewise it is also lower than that of Srinivas et al, (2013) who recorded 17.7% prevalence. Baba et al (2009) reported 0.6% IgM seropositivity which is lower than the results from this study.…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence rate of 17.2% from this study is lower than what Faneye et al (2013) who reported 30.8% among the population studied in Nigeria. Likewise it is also lower than that of Srinivas et al, (2013) who recorded 17.7% prevalence. Baba et al (2009) reported 0.6% IgM seropositivity which is lower than the results from this study.…”
Section: Discussionmentioning
confidence: 56%